An Analysis Genotype Inheritance in a Trihybrid Cross by Applying a Diagonalization of Matrix Method - Azis, Dorrah; Syanur, Marsela Nuvela; Amanto, Amanto; Zakaria, La (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aimed to find out the formulation of inheritance to know the genotype of the n-th generation in trihybrid crosses with controlled parent genotypes and analyze them by applying the diagonalization of a matrix. Matrix diagonalization makes it easier to find out the inheritance genotype of the n-th generation in trihybrid to obtain superior offspring compared with crossing it one by one, which requires a lot of time and cost. Based on the analysis, an equation for the probability of inheritance was obtained for 27 genotypes of the n-th generation, and the resulting offspring in an infinite generation are likely to have the TTKKBB genotype.